(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The problem of anesthesia for delivery in the abdominal cavity has long been solved. At the same time, spinal (SA) and epidural anesthesia (EA), as well as general multicomponent anesthesia (GA) with mechanical ventilation are used as anesthetic assistants [1]. Each of these methods has its advantages and disadvantages, indications and contraindications. In modern obstetrics, the choice of anesthesia for caesarean section is of particular importance, as it should contribute to adequate protection of the pregnant woman from surgical stress and create optimal conditions for the adaptation of the fetus in the perioperative and neonatal period. In modern obstetrics, the anesthesiologist plays a larger role than simply providing anesthesia for caesarean section and postpartum care [2]. Caesarean section is one of the most common birth operations used in obstetric practice. The frequency of this delivery operation is increasing all over the world, including in the Republic of Uzbekistan. The problem of sedation in obstetric intensive care units is undoubtedly of scientific and practical importance [3]. Sedation can reduce the risk of congenital complications and allow patients to recover more quickly.Most often, a component of drug sedation is a local blockade performed by an anesthesiologist, because an important task of sedation is to achieve and maintain a level of anesthesia that eliminates involuntary movements and increases in blood pressure, heart rhythm disturbances, and timely treatment. [4]. Almost all patients in the intensive care unit are adequate for various reasons, including the need for invasive procedures, disruption of sleep and wake rhythms, the severity of the general condition and the need for respiratory support. level requires sedation [5].